Evaluation Of Drug Prescription Base On Hospital Formularium In The Outpatient Installation In A Hospital Tasikmalaya Region - Ruhaniyyah, Ai Syifa (Ad-Dawaa : Journal of Pharmacy, 2024)
Hospital Formulary is a document that regulates pharmaceutical services in a Hospital, containing a list of drugs and drug use policies in the Hospital as well as instructions for their use. The Hospital Formulary has a very important role in the use of drugs for patients in the Hospital, in addition to functioning to ensure the quality and accuracy of drug use. The purpose of this study was to evaluate the suitability of prescription writing in the Outpatient Installation based on the hospital formulary in a hospital in the Tasikmalaya area. The method used in this study is a non-experimental type of research that is descriptive in nature with data collected retrospectively. The analysis period was carried out for one year from January to December. The results of the study showed that the percentage of prescription suitability by calculating the prescribed drug items was in the range of 89% -95%. The highest percentage of drug item suitability was achieved in September and November, which was 95%. The average percentage of drug item suitability during January-December was 92%. From the results of this study, it can be concluded that prescriptions in a Hospital in the Tasikmalaya Area show compliance with the Hospital Formulary